APPLICATION OF NATURAL COLOR MIXED AND NaCl AS MORDANT ON WOOD FIBER USING SIMULTANEOUS MORDANTING - Bogoriani, Ni Wayan (International Journal of Biosciences and Biotechnology; Vol 3 No 2 (2016), 2016)
Wood is one of the few materials that is highly exploited by humans, resulting in increasing usage of low quality wood. High demand and usage on high-quality wood causing heavy reduction of its availability. To increase artistic value of low quality wood, staining on the surface of the wood need to be done. This research aims to apply a mix of natural pigments (Gambier- Piper betle leaves- Areca seeds) and NaCl salt as the mordant on the surface of Albesia wood fiber and test the physical and chemical dye properties with 1% detergent. This study uses a mixture of natural dyes (Gambier- Piper betle leaves- Areca nut) with various concentrations and salt as auxiliaries, carried out with the simultaneous method of mordanting. This study was divided into 7 groups. Differences in mean between groups were tested using One Way ANOVA followed by Post Hoc LSD, which revealed statistically significant test when p value < >0.05. The results showed that there were significant differences of natural dyes mixed applications (Gambier- Piper betle leaves- Areca seeds) in the ratio of 5.0: 3.0: 3.0 to 0.5 g of salt as auxiliaries and 10 minutes of immersion with the simultaneous method of mordanting. Ratio of the dye mixture, on the surface of the wood causes brown color and has the highest absorption average of 0.19 gram and the durability of the dye showed the highest seen from the appearance of color and mix of the missing mass. It can be concluded that the best application is with a mixture of natural dyes and the addition of 0.5 g of NaCl salt on the surface of Albisia wood fiber with the simultaneous method of mordanting and also based on the durability of the dye test is a ratio of 5.0: 3.0: 3.0.
Keywords: Areca seeds, Piper betle leaves, gambier, NaCl, mordant